(untitled) (Cambridge, U.K.,New York, NY,London, 2000)
How does an understanding of the behavior of a given animal species contribute to its conservation? The answer has profound consequences for our efforts to conserve endangered species. Behaviour and Conservation links the extraordinary advances in behavioral ecology over the past thirty years with the new discipline of conservation biology. It shows how an evolutionary approach can help solve problems in practical conservation, and suggests a new direction for behavioral ecology. Leading authorities in animal behavior address the ways in which behavior and conservation interact, investigating the conservation impact of people, habitat loss and fragmentation, threats to wild populations of animals, conservation priorities, and the use of behavioral approaches for conservation applications
Keywords: Conservation biology,Animal behavior,Bảo tồn hệ sinh thái